2015
DOI: 10.18410/jebmh/2015/687
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Correlation of Diabetic Retinopathy in Relation to Diabetic Nephropathy in Type Ii Dm Patients

Abstract: Diabetes mellitus is one of the most common metabolic disorders of multiple etiology. The multisystem effects of diabetes such as retinopathy, nephropathy, neuropathy and cardiovascular diseases have an important impinging on the working age individuals in our country. Diabetic Retinopathy (DR) is one of the leading causes of blindness in the world that increases the chance of losing vision to about 25 times higher compare to normal individuals. Diabetic Nephropathy (DN) is the major life-threatening complicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The above data was compared with other studies like where there was a prevalence of 81.5% with abnormal lipid levels in patients with diabetic nephropathy, this was also compared with another study where elevated serum lipids was a risk factor for the development of diabetic nephropathy, in another study where the total cholesterol (p=0.01), LDL cholesterol(p=0.009) and triglycerides (p=0.224) were higher in microalbuminuria group than normoal buminuria group and the differences were statistically highly significant except for HDL in males (p=0.154) and triglycerides(p=0.224), in a study by there was no significant association between abnormal lipid levels and nephropathy, in a study (UKPDS 74) where dyslipidemia (total cholesterol (p=0.04), HDL cholesterol (p=0.02), LDL cholesterol (p=0.08), triglycerides (p<0.0001) ) had a significant association with albuminuria or nephropathy, in a Japanese study by dyslipidemia has no significant association with eGFR (p=0.26) but had a significant association with albuminuria (p<0.005). 9,10,15,16,18,19 The present study shows that abnormal elevated serum lipid levels or dyslipidemia had a significant association with diabetic nephropathy.…”
Section: Dyslipidemia In Type 2 Diabetics With Nephropathymentioning
confidence: 49%
“…The above data was compared with other studies like where there was a prevalence of 81.5% with abnormal lipid levels in patients with diabetic nephropathy, this was also compared with another study where elevated serum lipids was a risk factor for the development of diabetic nephropathy, in another study where the total cholesterol (p=0.01), LDL cholesterol(p=0.009) and triglycerides (p=0.224) were higher in microalbuminuria group than normoal buminuria group and the differences were statistically highly significant except for HDL in males (p=0.154) and triglycerides(p=0.224), in a study by there was no significant association between abnormal lipid levels and nephropathy, in a study (UKPDS 74) where dyslipidemia (total cholesterol (p=0.04), HDL cholesterol (p=0.02), LDL cholesterol (p=0.08), triglycerides (p<0.0001) ) had a significant association with albuminuria or nephropathy, in a Japanese study by dyslipidemia has no significant association with eGFR (p=0.26) but had a significant association with albuminuria (p<0.005). 9,10,15,16,18,19 The present study shows that abnormal elevated serum lipid levels or dyslipidemia had a significant association with diabetic nephropathy.…”
Section: Dyslipidemia In Type 2 Diabetics With Nephropathymentioning
confidence: 49%
“…During the mean follow up of 6.6 years, they found that patients with microalbuminuria and estimated GFR >60 mL/min/1.73 m 2 had a threefold increase in risk compared with those with normoalbuminuria and estimated GFR 30-59.9 mL/min/1.73 m 2 . Reddy et al 1 Almost three fourth (73.4%) patients was found diabetic retinopathy in diabetic retinopathy and 27(54.0%) in without diabetic retinopathy. e di erence was statistically signi cant (p<0.05) between two groups.…”
Section: Discussionmentioning
confidence: 92%
“…Chen et al 19 reported that a microalbuminuria threshold of 10.7 mg/24 h, which was within the conventional 'normal range', can predict the increased risk for diabetic retinopathy development. Reddy et al 1 20 noted that 4 of 8(50%) cases without DR had DN. It should be pointed out that absence of retinopathy cannot exclude the presence of Diabetic Nephropathy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations